School-level variables that enhance student achievement: examining the role of collective teacher efficacy and organizational citizenship behavior - Erdogan, Ufuk; Dipaola, Michael F.; Donmez, Burhanettin (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this study was to examine the relationships among collective teacher efficacy (CTE), organizational citizenship behavior (OCB), and student achievement in Turkey. Design/methodology/approach Multilevel analysis was conducted to investigate how school-level variables, including collective teacher efficacy, organizational citizenship behavior, and school socioeconomic status, affect student achievement. Data were collected from 674 teachers and 7,173 students embedded in 57 schools. Findings Results showed significant variation in mean student achievement between schools, with approximately 20% of the variance in mean achievement occurring between-schools. After controlling for school Socioeconomic status (SES), CTE and OCB significantly predicted school mean achievement scores and explained approximately 45% of the between-schools variance in achievement. Practical implications The results of the study verified that CTE and OCB are important school-level variables that contribute to the achievement of students. It reemphasizes the significance of these constructs in creating the conditions to foster student achievement even in low-SES schools. Originality/value This was the first attempt to examine the relationships between CTE, OCB and student achievement in Turkey. The findings of this study may contribute to the international knowledge base by investigating the relationship between CTE, OCB, and student achievement in a collectivist cultural context.
Keywords: Collective teacher efficacy; Organizational citizenship behavior; Student achievement; School improvement; Multilevel modeling